Drones and Targeted Killing in the Middle East and Africa : an appraisal of American counterterrorism policies - Rinehart, Christine Sixta, 1980- (Lanham: Lexington Books, 2016)
"The use of drone warfare has become a controversial foreign policy weapon to keep the United States safe from further terrorist attacks. This book is an assessment of American targeted killing practices through drone warfare in the Middle East and Africa, including Afghanistan, Iraq, Libya, Pakistan, Somalia, Syria, and Yemen."--Provided by publisher.
Keywords: Drone aircraft--Government policy--United States; Targeted killing--Government policy--United States; Terrorism--Prevention--Government policy--United States; United States--Military policy--History--21st century; United States--Foreign relations--21st century